2008
DOI: 10.1091/mbc.e07-05-0480
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 2-Integrin αvβ3 Binding Is Required for Mesenchymal Cell Invasive Activity but Not Epithelial Locomotion: A Computational Time-Lapse Study

Abstract: Cellular invasive behavior through three-dimensional collagen gels was analyzed using computational time-lapse imaging. A subpopulation of endocardial cells, derived from explanted quail cardiac cushions, undergoes an epithelialto-mesenchymal transition and invades the substance of the collagen gels when placed in culture. In contrast, other endocardial cells remain epithelial and move over the gel surface. Here, we show that integrin ␣v␤3 and matrix metalloproteinase (MMP)2 are present and active in cushion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 65 publications
4
42
0
Order By: Relevance
“…Such fragments block protease activation by competing with MMP-2 for binding to ␣V␤3. The binding of MMP-2 to integrin ␣V␤3 via its hemopexin domain is crucial for mesenchymal cell invasive activity (28). Likewise, high local concentrations of active MMP-14 on the cell membrane of metastatic cancer cells play important roles in cell migration (29 -31).…”
Section: Discussionmentioning
confidence: 99%
“…Such fragments block protease activation by competing with MMP-2 for binding to ␣V␤3. The binding of MMP-2 to integrin ␣V␤3 via its hemopexin domain is crucial for mesenchymal cell invasive activity (28). Likewise, high local concentrations of active MMP-14 on the cell membrane of metastatic cancer cells play important roles in cell migration (29 -31).…”
Section: Discussionmentioning
confidence: 99%
“…ROS in tumors can influence the function of MMPs and the inflammatory responses at tumor sites generates large amounts of ROS produced by activated neutrophils and macrophages, and Rupp et al [248] have shown that the binding of MMP-2 to integrin α ν β 3 via its hemopexin domain is crucial for mesenchymal cell invasive activity. Several investigators [249][250][251] have shown that high local concentration of active MMP-14 on the cell membrane of metastatic cancer cells play very important roles in cell migration.…”
Section: Matrix Mellalloproteinases (Mmps)mentioning
confidence: 99%
“…43 In addition, signaling through cell-matrix receptors could be modified in less remodeled matrix. 44 Alternatively, neo-epitopes, cryptic in intact collagen fibrils, might be exposed after MMP2 cleavage, thereby providing new morphogenetic signals. 45 These different mechanisms are obviously not exclusive.…”
mentioning
confidence: 99%